COMPARATIVE ANALYSIS BETWEEN BIFACIAL AND MONOFACIAL SOLAR PANELS USING PV*SOL SOFTWARE (ETIMA, 2024)
Traditional solar panels commonly used in today’s solar power projects are monofacial i.e., with solar cells only on one side of the panels. Recently, many solar panel producers have improved their panel designs by introducing so-called bifacial solar panels which feature solar cells on both sides of the solar panel. Producers claim that the bifacial solar panels, regarding energy generation, typically overperforms the traditional monofacial solar panels by about 5.5%, with additional investment cost between 10% and 25%, which strongly depends on the producer and the size of the project.In this paper, the authors made a simulation and comparative analysis between bifacial and monofacial solar panels using PV*SOL simulation software. The simulation was done on a solar power project with an installed capacity of 1 MW using exact solar insolation values for the exact geographical location. Typical bifacial and monofacial half-cell solar panels available at the local market were used for the analysis. For enhancing the analysis, two common placements of the panels were utilized, ground placement, and rooftop placement parallel with the roof at the same inclination (pitch) and orientation (azimuth). Obtained results using PV*SOL simulation software for both panels and both placements are presented with accompanying discussion. For ground placement, bifacial solar panels resulted in increased energy generation of approximately 2.5%, while for rooftop placements the amount of the increased energy generation was negligible. Ground-placed bifacial solar panels have increased energy generation all year around, while rooftop bifacial solar panels provide larger energy generation only during summer months, from June to August. For the rest of the year the energy generation difference, although in favor of bifacial over monofacial solar panels, was still negligible
Keywords: Photovoltaics; monofacial solar panels; bifacial solar panels; PV*SOL; renewables